MEWUJUDKAN GOOD GOVERNANCE MELALUI PELAYANAN PUBLIK DALAM ERA OTONOMI DAERAH - Fitriani, Dini Rizal (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2017)
Good Governance arrange good governance, public service and also autonomy of area a global phenomenon which in principle converse to hit how government can realize good governance through public service in autonomous era [of] area. conception of Good governance leave from concept of Welfare State having a purpose national that is secure and prosperous socialize in general without there gap. Prosperity formed] and also existed through service of public given by government primaly ( prima service). governmental Elementary reality as public steward ( public servant) have to can be felt by all coat socialize. drawn nearly governmental with governed ( desentralisasi) expected can reply and also fulfill expectation and also the requirement socialize without aside from